Aplicacion de la fluorescencia de Rayos X al analisis de pinturas antiincrustantes - Miniussi, Claudio L. (1969)
The X Ray fluorescence can he applied successfully to the determination of copper and arsenic, without previous separation, ii antifouling paints. The attack of the sample is made with $latex NO_{3}H-SO_{4}H_{2}$, and spectrométrie determination is performed with the solution, adding potassium bromide as internal standard. It works with an anode of chromium and crystal of FLi, using Kα lines for copper and arsenic, and Kβ for bromide (internal standard). The relative error is 2,1 % for arsenic and 1,6 % for copper.